2022
DOI: 10.17153/oguiibf.1098419
|View full text |Cite
|
Sign up to set email alerts
|

Çevresel, Sosyal ve Kurumsal Yönetim (ESG) Performansının Piyasa Değeri Üzerindeki Etkisi: Firma Büyüklüğünün Rolü

Abstract: Çalışmada gelişmekte olan piyasalardan Borsa İstanbul’da (BIST) işlem gören işletmelerin çevresel, sosyal ve kurumsal yönetim (ESG) kriterleri konusundaki performanslarının piyasa değeri ile ilişkisi ve bu ilişkide firma büyüklüğünün rolü araştırılmaktadır. Ohlson (1995) değerleme modelini temel alan genişletilmiş statik doğrusal panel regresyon modeli tahminlerinden izleyen sonuçlar elde edilmiştir. Firma büyüklüğü, ESG kriterlerinin piyasa değeri üzerindeki etkileri bakımından firmalar arası farklılıkları aç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For example, Düzer and Önce (2019) examined the sustainability reports of 30 companies traded on the BIST between 2008 and 2014 and investigated their ESG performances over the economic, environmental, and social performance sub-components in line with GRI reporting principles. Moreover, Kulalı (2022) investigated the relationship between the ESG performance of the firms traded in Borsa Istanbul and the market value and the role of firm size in this relationship between the years 2016-2020. The researcher found that both ESG criteria and ESG components had a significant and positive effect on market value.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Düzer and Önce (2019) examined the sustainability reports of 30 companies traded on the BIST between 2008 and 2014 and investigated their ESG performances over the economic, environmental, and social performance sub-components in line with GRI reporting principles. Moreover, Kulalı (2022) investigated the relationship between the ESG performance of the firms traded in Borsa Istanbul and the market value and the role of firm size in this relationship between the years 2016-2020. The researcher found that both ESG criteria and ESG components had a significant and positive effect on market value.…”
Section: Discussionmentioning
confidence: 99%
“…The study found a positive relationship between ESG and firm value and that firm size plays a moderating role in the relationship between both firm value and performance. Similarly, Kulali (2022) examined the relationship between ESG and market value in Borsa Istanbul and the role of firm structure in this relationship and found a positive relationship between ESG and firm value. The study also showed that positive effects are greater in relatively larger companies.…”
Section: H1: Esg Activities Positively Affect Firm Performancementioning
confidence: 99%